Hubungan Penggunaan Gadget Dan Stres Dengan Insomnia Pada Remaja Kelas Akhir Di SMK Kesehatan Logos Kabupaten Bogor Tahun 2023 - Nazwa Syifa Azzahra; Mustopa Mustopa; Rindu Rindu (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Sleep is something that must be fulfilled, if it it fulfilled it will cause disturbances in a person's biology and psychology. Many factors influence insomnia, including disease, fatigue, environment, stress, medication, diet, and alcohol and nicotine. The use of gadgets can also affect insomnia because addiction to bluelight gadgets will shift your sleep rhythm, causing insomnia. This research aims to determine the relationship between intensity of gadget and stress with insomnia in final class adolescents at Logos Health Vocational School. The research method used is Cross-Sectional. involving 99 final grade students of Logos Health Vocational School. By using the Chi-Square Statistical Test and the results of this research, the P value = 0.001, which means that the value is <0.05. Conclusion: There is a relationship between the intensity of gadget and stress and insomnia in final class adolescents at Logos Health Vocational School, Kabupaten Bogor in 2023. The results of this research are expected to provide benefits for parents and schools in efforts to prevent the occurrence of insomnia, as well as handling stress and use. gadgets.